СOMPARATIVE ANALYSIS OF THE PERFORMANCE CHARACTERISTICS OF INDUSTRIAL HYDROTREATMENT CATALYSTS (American Journal of Technology and Applied Sciences, 2025)
Comparative analysis of hydrotreatment catalysts revealed notable differences in their performance levels. The study demonstrated that the industrial hydrotreating catalysts type-ACM (alumina–cobalt–molybdenum) and ANMS (alumina–nickel–molybdenum–silicate) manifest a significantly lower activity in the thiophene hydrodesulfurization reaction. Specifically, their performance characteristics were roughly two times lower compared to the most effective similar catalysts produced abroad. This was observed both before and after sulfidation with hydrogen sulfide, suggesting that while sulfidation does improve their performance, it does not bring them to the level of their more advanced samples produced abroad. The findings highlight the need for further optimization of catalysts to enhance their performance and competitiveness in industrial applications.